Keajaiban Lafadz Istigfar Membentuk Karakter Siswa - Galih Maulana Hendrawan; Dien Nurmalina Malik (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The phrase istighfar in forming and strengthening character education based on AIK (Al-Islam and Muhammadiyah) values. Istighfar as an expression of asking for forgiveness from Allah SWT has a deep spiritual meaning and strong relevance in forming a person's character that is noble, honest, and responsible. Through a descriptive qualitative approach, the author describes the importance of internalizing the phrase istighfar in everyday life as a means of introspection, self-improvement, and moral strengthening. AIK-based character education that integrates the practice of istighfar is expected to produce people who are not only intellectually intelligent, but also spiritually and socially superior. Thus, istighfar is not only a ritual of worship, but also a medium for self-transformation towards a perfect human being.